PENGGUNAAN MEDIA KARTU KATA GAMBAR DI KELAS III SDN 04 KOTO BARU - Ayu Ningsih Almirus; Rusdi Indra Hasibuan; Dila Santika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of beginning reading skills among third-grade students at SDN 04 Koto Baru. Some students experienced difficulties in recognizing letters, reading syllables, words, and simple sentences, as well as understanding the content of reading texts. In addition, the learning process was still dominated by the lecture method and had not optimally utilized engaging instructional media, resulting in low student participation and motivation. Therefore, this study aimed to determine the effect of using picture word card media on the beginning reading skills of third-grade students at SDN 04 Koto Baru.This study employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The population and sample consisted of all 24 third-grade students of SDN 04 Koto Baru selected through a saturated sampling technique. The research instruments included a beginning reading test, a questionnaire, and documentation. The collected data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-Test with the assistance of SPSS software.The results indicated that the students' beginning reading skills improved after the implementation of picture word card media. The hypothesis testing showed that the significance value (Sig. 2-tailed) was less than 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Therefore, it can be concluded that the use of picture word card media has a significant effect on the beginning reading skills of third-grade students at SDN 04 Koto Baru. This instructional media was proven to improve students' participation, learning motivation, and reading achievement, making it a suitable alternative for teaching Indonesian language, particularly in improving beginning reading skills in elementary schools.